As proposições do Banco Mundial para as políticas de educação infantil no Brasil (1990-2010) - Bueno, Cristiane Aparecida Ribeiro (2012)
This work has investigated, in the scope of the educational policies for the Childhood Education in Brazil, in the decades of 1990-2010, the convergences and the deviations in relation to the propositions of the World Bank. It was considered, in the research process, that the World Bank, from the decade of 1970 on, has supported the investment in human capital, articulated with the directed social policies to the basic requirements, focused on the socially vulnerable population, targeting poverty relief. For the World Bank the beginning of the childhood education attendance promotes the skills and the abilities, contributing towards the increase of the future income. Thus, it was evidenced that the educational policies for the Childhood Education, elaborated in the decades of 1990- 2010, in Brazil, expressed the propositions of the World Bank of the basic requirements satisfaction related to the human capital theory, targeting poverty relief. Brazilian Childhood Education policies, conceived as the first stage of acquisition of skills and abilities, also express the propositions of the World Bank regarding the insertion in the labor market, once it motivates the citizens productivity